2004
DOI: 10.1074/jbc.m402778200
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of the Na,K-ATPase in Cell Membranes

Abstract: The higher order oligomeric state of the Na,K-ATPase ␣␤ heterodimer in cell membranes is the subject of controversy. We have utilized the baculovirus-infected insect cell system to express Na,K-ATPase with ␣-subunits bearing either His 6 or FLAG epitopes at the carboxyl terminus. Each of these constructs produced functional Na,K-ATPase ␣␤ heterodimers that were delivered to the plasma membrane (PM). Cells were simultaneously co-infected with viruses encoding ␣-His/␤ and ␣-FLAG/␤ Na,K-ATPases. Co-immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
1
20
0
3
Order By: Relevance
“…Plasmid construction, cell culture, and transfection Sheep Na + /K + -ATPase a and b open reading frames were PCR amplified from pFASTBAC dual-Na + /K + -ATPase plasmid, which was cloned and characterized as described previously (Gatto et al, 2001;Laughery et al, 2003;Laughery et al, 2004). For heterologous expression of both a-and b-subunits concomitantly, Na pump a-mcherry and b-fragments were cloned into pBud v4 (Invitrogen, Carlsbad, CA) into NotI/KpnI and SalI/XbaI sites, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid construction, cell culture, and transfection Sheep Na + /K + -ATPase a and b open reading frames were PCR amplified from pFASTBAC dual-Na + /K + -ATPase plasmid, which was cloned and characterized as described previously (Gatto et al, 2001;Laughery et al, 2003;Laughery et al, 2004). For heterologous expression of both a-and b-subunits concomitantly, Na pump a-mcherry and b-fragments were cloned into pBud v4 (Invitrogen, Carlsbad, CA) into NotI/KpnI and SalI/XbaI sites, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…5), even when diluted 10-fold, or when run in DDM at 15 mg/ml, the monomeric species in DDM is stable, and does not appear to be in a mobile equilibrium with other molecular species. Our findings are not inconsistent with recent work, showing by immunoprecipitation that Na ϩ ,K ϩ -ATPase expressed in baculovirus-infected insect cell membranes, and dissolved in DDM, can exist as oligomers of the ␣/␤ heterodimer, if we consider the oligomers detected in the void volume by HPLC, the presence of minor heavier species in addition to monomer in the sedimentation profiles, and the tendency of the protein to slowly auto-associ- ate with time (data not shown) (47). Of course, the characterization of Na ϩ ,K ϩ -ATPase as a monomeric species in DDM does not preclude that other oligomeric species exist in the membrane.…”
Section: Fig 8 Inactivation Of Namentioning
confidence: 99%
“…While early studies concluded that the minimal functional unit is an ␣-␤ protomer (24), the monomeric or oligomeric nature of the functional Na-K-ATPase unit is not yet fully established. Recent evidence either suggests that plasma membrane ␣-␤ protomers of Na-K-ATPase are mostly monomeric (29) or oligomeric (27). It should be mentioned that in transfected cells, c-myc-tagged ␣ 1 -subunits are overexpressed and compete with endogenous ␣-subunits for limiting ␤-subunits.…”
Section: Increasing Intracellular Namentioning
confidence: 99%